Physico-Chemical Studies on the Binary Mixture of Chloroform + Cyclohexane Liquid Mixtures at 303.15, 308.15 and 313.15 K - Vanathi1, V.; Mullainathan1, S.; Nithiyanantham3, S. (Asian Journal of Chemistry, 2013)
Ultrasonic velocity, density and viscosity of the binary mixture of chloroform + cyclohexane were measured at 303.15, 308.15 and 313.15 K. The thermodynamical parameters such as adiabatic compressibility (b), intermolecular free length (Lf), free volume (Vf), internal pressure (pi), acoustic impedance (Z), molar sound velocity (R) and molar compressibility (W) have been obtained from the experimental data for all the mixtures, with a view to investigate the exact nature of molecular interaction. Adiabatic compressibility and intermolecular free length decrease with increase in concentration and temperature. The other parameters show almost increasing concentration of solutes. These parameters have been further used to interpret the molecular interaction part of the solute and solvent in the mixtures.